Dynamics of Goals and Methods of Forecasting Social Phenomena and Processes - Zakharovna Michurina, Frida; Vyacheslavovich Klimov, Dmitriy (International Journal of Engineering and Technology, 2018)
The article shows the differentiation of new directions of forecasting, differing in goals and methods of implementation. The first direction reflects the formation of private forecasts and the selection of necessary innovations on their basis. The second one is due to the formation of globalization processes, reflects the need to take into account their influence and serves to make decisions in the field of economic policy. The third direction of predictive research is based on studying the living conditions of the population and aimed at achieving social well-being. The methodological approach combining extrapolation and standards (of the need and potential) in the process of forecasting is positioned in the article as appropriate.Â